The Effect of Maltodextrin Concentration and Roasting Time on the Physicochemical and Sensory Characteristics of Nori Snack Made from Sea Grape (Caulerpa sp.) - Anggita Ulfia Savitri; Jariyah Jariyah; Ratna Yulistiani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Nori snack is dried edible seaweed, which is made from drying and roasting so its texture is crispy and thin. Commercial nori snack is usually made from Porphyra seaweed which cannot be cultivated in Indonesia. Sea grapes (Caulerpa sp.), a local seaweed that is widely cultivated in Indonesia, have the potential to be used as an alternative material for nori snacks. The formation of nori with the addition of Eucheuma cottonii gives a nori snack texture that tends to be elastic and less crunchy. Crispness is the main parameter to consider in choosing nori snacks. The addition of maltodextrin as a texture enhancer is needed to give a compact and crispy texture, and roasting time can also increase the level of crispness in nori products. This study aims to determine the physicochemical and organoleptic characteristics of sea grape nori snacks (Caulerpa sp.). Factorial completely randomized design (CDR) with two factors. Factor I was the maltodextrin concentration (1, 2, and 3%), while factor II was a roasting time (1, 2, and 3 minutes) and two replications. The data were analyzed using Analysis of Variance (ANOVA) and followed by Duncan’s New Multiple Range Test (DNMRT) at the 5% significance level. The best treatment was the addition of 3% maltodextrin and a roasting time of 3 minutes. The results obtained were a moisture content of 6.13%, ash content of 12.45%, protein content of 17,07%, a yield of 6.22%, a breaking strength of 5.23%, and an average score of preference for the aroma of 2.8 (dislike), the colour of 3.5 (standard), the taste of 4.05 (like), and crispness of 4.10 (like).